Microangiopathic Anemia of Acute Brucellosis – is it a True TTP? - Amir Kuperman (Mediterranean Journal of Hematology and Infectious Diseases)
Thrombotic thrombocytopenic purpura (TTP) is a severe disease, potentially fatal, if not diagnosed and treated promptly. TTP is clinically characterized by the pentad of thrombocytopenia, Coombs-negative hemolytic anemia, fever, renal abnormalities and neurological disturbances. Advances in recent years have delineated the molecular mechanisms of acquired and hereditary TTP. Many infectious organisms have been reported to be associated with TTP, especially mycoplasma, but only 6 cases of Brucella infection associated with thrombotic microangiopathy were reported. We describe a young woman who presented clinically with TTP following acute infection with both Brucella melitensis and Brucella abortus. The patient completely recovered after an aggressive therapy with plasmapharesis, high-dose corticosteroids and appropriate antimicrobial therapy. Since measurement of ADMTS13 activity and neutralizing antibodies is now available, and in none of the reported cases of brucellosis with thrombotic microangiopathy (including the present report) were tested, we recommend this work-up in future cases for better understanding of this rare association.